Municipal finance, density, and economic development. Empirical evidence from a global sample of cities - Kamiya, Marco; Scuderi, Raffaele; Tesoriere, Giuseppe (TeMA - Journal of Land Use, Mobility and Environment, 2022)
This research focuses on how population density may influence the municipal expenditure using a global dataset from UN-Habitat. Specifically, we test its role on different budget categories, including sanitation, waste, water, affordable housing, and security. We find that in general density is likely to be correlated with expenditure. This evidence is not robust across the considered expenditure categories. Rather, population density is likely to influence specific budget items and its explanatory power varies as we consider different measures of it. Among control variables, we point out the significance and magnitude of the regressors related to economic development, which in some cases matters more than density in explaining some expenditure categories. Findings suggest that making cities denser can be a valuable option of urban policy, if the target is expenditure optimization. Nonetheless, this works only when it is combined with a mix of other factors, and location is also considered.